Neuromodulatory effects of high-definition theta transcranial alternating current stimulation on the parietal cortex: a pilot study of healthy males - Chen, Xixi; Wu, Yuwei; Shi, Xiaolong; Zhou, Zhiqing; Feng, Tingyi; Ren, Meng; Li, Yuanli; Shan, Chunlei (Frontiers in Neuroscience, 2023)
Transcranial alternating current stimulation (tACS) can regulate brain functions by modulating endogenous brain rhythms. Theta neural oscillations are associated with memory function. In particular, theta neural oscillatory power evoked in the parietal cortex is closely related to memory retrieval processes. In this study, the immediate effects of high-definition theta transcranial alternating current stimulation (HD θ-tACS) on human left parietal cortex were investigated using short latency afferent inhibition (SAI) and electroencephalogram (EEG). Ten subjects participated in this study. We used 6-Hz HD-tACS to stimulate the left parietal cortex for 15 min. SAI was calculated, and the nonlinear dynamic analysis of EEG was performed to analyze the neuronal function after HD θ-tACS. The results showed a significant decrease in the SAI(p < 0.05), while the left frontoparietal network was reinforced, leading to brain lateralization after HD θ-tACS. In the task state, the F3 in approximate entropy showed a significant upward trend after treatment (p < 0.05). The cross-approximate entropy showed a significant decrease in the connection between C3-C4 and P3-P4 following the intervention (p < 0.05) in the resting eyes-open state and task state.In conclusion, HD θ-tACS could alter cholinergic transmission and cortical excitability between the parietal and motor cortices, as well as reinforce the frontoparietal network and the left lateralization phenomenon, which may facilitate memory formation, encoding, and consolidation.